Use of the lower extremity functional test to predict injury risk in active athletes - Shi, S.; Shi, X.; Yang, Z.; Chen, Z.; Witchalls, J.; Adams, R.; Han, J. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: The purpose of the current study was to assess the reliability and validity of the lower extremity functional test (LEFT) for predicting low back and lower limb injury in active athletes. METHODS: Seventy athletes (45M, 25F; mean age: 21±2 years) from seven different sports volunteered. The LEFT was a battery of five weight-bearing functional movements involving different movement planes, directions, modes, and at varying intensities. Both legs were assessed in a random order and each athlete was given both movement quality and associated symptom scores. Intratester, intrarater and inter-rater reliability were evaluated. Participants were followed up for 12 months, and their exposure to sport and subsequent injuries were recorded. Independent samples t-tests were performed to determine if a significant difference existed in LEFT scores between injured and non-injured athletes. Receiver operating characteristic (ROC) curve analysis was employed to assess the instrument`s capacity to predict injury. RESULTS: The intratester reliability ICC2, 1 was 0.875. The ICC2, 3 of intrarater reliability was 0.953 and the inter-rater reliability was 0.949, respectively. Nineteen participants had an injury in the low back or lower limb within the following 12 months. Injured athletes had significant lower movement quality and symptom scores of the LEFT than non-injured (t=4.278, P=0.000, Cohen`s d=1.2; t=3.654, P=0.001, Cohen`s d=1.3, respectively). When movement quality or symptom score alone was included in the ROC analysis, the area under the ROC curve (AUC) scores were 0.772 (P=0.000, 95% CI: 0.653-0.891) and 0.771 (P=0.001, 95% CI: 0.638-0.905), respectively. When movement quality and symptom scores were combined to predict injury, the AUC discrimination score was 0.853 (P=0.000, 95% CI: 0.754-0.953), resulting in 85.3% of cases being correctly predicted as low back or lower limb injured/noninjured. CONCLUSIONS: The findings from the current study suggest that the LEFT appears to be a reliable and valid functional assessment tool for predicting low back or lower limb injury risk in these college athletes, especially when movement quality and symptom scores were used in combination.